COMPARING HAMSTRING FLEXIBILITY BETWEEN THE TRANSTIBIAL PROSTHETIC WEARERS AND THE CONTROL SUBJECTS AND ASSESSING FACTORS ASSOCIATED WITH HAMSTRING FLEXIBILITY (Proceedings of the World Disability & Rehabilitation Conference, 2019)
Hamstring flexibility is necessary for mobility in transtibial prosthetic wearers. The aim of this study was to compare hamstring flexibility of transtibial prosthetic wearers and non-amputees and to assess factors associated with hamstring flexibility. A descriptive comparative study was carried out with participation of 50 male transtibial amputees who were prosthetic wearers and 50 male control subjects who were non-amputees. Study population mean age was 55.66 years (SD ±11.455) in transtibial prosthetic wearers while it was 51.28 years ( SD ±10.784) in control subjects. Data related to amputation were collected by using an interview-administered questionnaire and hamstring flexibility was assessed using the back saver sit and reach test. Statistical analysis was done by using statistical package for social sciences 16.0 version. The study revealed that, hamstring flexibility has significant relationship (p=0.001) with transtibial prosthetic wearers and control subjects. Further, the younger age (p=0.002) and participation of prosthetic rehabilitation programme (p=0.005) have significant relationship with hamstring flexibility. whereas it has no significant relationship (p>0.05)  with educational level, engaging in sports activity, reason for amputation, post prosthetic period, timing of wear the prosthesis and duration of participation of prosthetic rehabilitation programme. . It can be concluded that hamstring flexibility of transtibial prosthetic wearers is lower than non-amputees. In addition to that, age below fifty and Prosthetic rehabilitation programme was associated with better hamstring flexibility among transtibial prosthetic wearers.
Keywords: Hamstring; flexibility; transtibial amputee; prosthesis; age; rehabilitation.